Michel Foucault se historiografiese benadering as lens in historiese ondersoeke - Mary-Anne Plaatjies van Huffel (Acta Theologica)
In the article the author argues that Foucault’s insights on the archaeological historiography, genealogy and discourse analysis can be used as a lens to write history as well as to deconstruct the existing historical sources. Foucault’s main thesis is that history is largely an illusion. Foucault contrasts effective historiography with traditional historiography. He is against the traditional scheme of historical research. Foucault’s archaeological historiography is a method of historical analysis that is free from the anthropological theme. In the article the following themes will be discussed: Foucault and post-structuralism, Foucault and the archaeological historiography, Foucault and the genealogical historiography, Foucault and discourse analysis, Foucault and the formation of objects of discourse, Foucault and the reading process and Foucault knowledge and truth, Foucault and power and discipline. Attention will also be given in this paper to Ricoeur’s notions on historiography.